Women’s use of news media and its influence on political engagement in post-Arab Spring countries - Chen, KhinWee; Al-Kandari, Ali A.; Alsaber, Ahmad (Frontiers in Political Science, 2025)
IntroductionThe Arab Spring uprisings (2010–2011) brought renewed attention to the political agency of women in the Arab world, often referred to as the “Twitter” or “Facebook” revolution due to the prominent role of social media. This study explores whether the type and format of news media consumption are significant predictors of political attitudes and behaviors among Arab women.MethodsUsing data from the 2013–2014 wave of the World Values Survey, we conducted statistical analyses to investigate the relationships between media exposure (categorized as vertical and horizontal media) and political attitudes and actions among Arab women.ResultsFindings indicate that both vertical and horizontal media formats significantly predict political attitudes. Notably, horizontal media use (e.g., social media and peer-to-peer platforms) was associated with more non-traditional political views. Additionally, consumption of internet-based news correlated strongly with increased political involvement. However, demographic variables, as well as perceptions of social institutions and political processes, exerted a stronger influence on political behavior than media type alone.DiscussionThe results suggest that while media choice plays a meaningful role in shaping political attitudes among Arab women, structural and institutional factors remain more decisive in motivating political action. These findings contribute to a nuanced understanding of media’s role in political mobilization in post-Arab Spring societies.